Euhybus newly recorded from Tibet with descriptions of two new species (Diptera: Empidoidea, Hybotinae) - Wang, Ning; Li, Zhu; Yang, Ding (Zootaxa, 2013)
Euhybus is newly recorded from Tibet. The following two species are described as new to science: Euhybus longiseta sp. nov. and E. nigritarsis sp. nov. A key to the known species from China is provided.